Demystifying the role of channel region in two-dimensional transistors. (7th April 2021) - Nipane, Ankur; Teherani, James T.; Ueda, Akiko
Abstract: Back-gated field-effect transistor (BGFET) structures are the most prominently used device platform to study the electrical properties of two-dimensional materials. These devices are widely modeled as Schottky barrier (SB)-MOSFETs assuming that the current flow is limited by the source-contact in the OFF state, while the channel limits the current in the ON state. Here, using an analytical model and drift-diffusion simulations, we show that the channel limits the overall current in the OFF state and vice versa, in contrast to past studies. Furthermore, we demonstrate how this renewed understanding helps to clarify the general underestimation of extracted SB height in experimental long-channel BGFETs.